24. INVESTING IN TRAGEDY: IMPLIKASI SUPLAI SENJATA CHINA TERHADAP SITUASI PASCA KONFLIK DI SUDAN, 2011-2014 - Vicky Nauli Barreto Simanjuntak; Reni Windiani; Andi Akhmad Basith Dir (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2016)
China is one of biggest actors in arms dealer in the world, and in Sudan, China has beenthe main supplier of weapons. However, Sudan is a country with a post-conflict situationwith weak government and is currently facing many rebel groups. The purpose of thisstudy is to determine the impact of the weapon circulation in post-conflict situations. Thisstudy is using the theory of Spoiler, which gives the emphasis of the resposibbility ofcertain actors in perpetruating or exacerbating crises in post-conflict region. China in thiscase, has been seen as the ‘opponent’ of the conflict as it continues supporting the sellingof the weapons in Sudan. The research revealas that the role of Chinese weapons in Sudanhas been very imminent in hampering the recovery processess in Sudan.